Pengaruh Stres Kerja Terhadap Kinerja Karyawan PT. Surya Madistrindo Area Operation (Ao) Bima - Kurniawan, Iwan; Mukminin, Amirul; Wulandari, Wulandari (Jurnal Ilmiah Mandala Education (JIME), 2021)
This research was aimed at determining the influence of work stress on the employees’ performance of PT. Surya Madistrindo Subsidiary, Marketing Unit, Palembang Area Operation.This research was conducted to 54 employees of the company. It treated work stress as the independent variable and the employees’ performance as the dependent variable. This is a quantitative research and it used a simple regression technique for analyzing the data. The data were collected through questionnaires.  The research results show that the regression computation pointed to this equation: Y =  26.083 + 0,400X. The X coefficient was 0,400 indicated that there occurred change in the work variable for one point, therefore, their performance increased as much 0,400.